Water contamination and health integration of exposure assessment, toxicology, and risk assessment - Wang, Rhoda G.M (Environmental science and pollution control series, 1994)
This practical reference examines every potential means of exposure to water contaminants, provides in-depth discussion on toxicology, explains the most up-to-date techniques for evaluating human health risk, and develops a methodology for assessing the cumulative absorbed dose of contaminants through all routes of exposure, including ingestion, inhalation, and dermal.